A mild form of dermatomyositis as a prodromal sign of lung adenocarcinoma: a case report. (December 2016) - Papakonstantinou, Eleni; Kapp, Alexander; Raap, Ulrike
Abstract Background Dermatomyositis is an idiopathic connective tissue disease characterized by specific cutaneous findings and inflammatory lesions in the muscle biopsy. An association between dermatomyositis and malignancy, including breast, ovarian, lung and colon cancer was recognized many years ago, with an incidence of malignancy in approximately 20 % of cases. Dermatomyositis is hypothesized to be an autoimmune reaction against factors or hormones secreted by the tumor; however, the exact autoimmune mechanism of the disease pathogenesis remains unknown. Case presentation Here we report a case of a woman with dermatomyositis who was diagnosed with lung adenocarcinoma in the setting of weight loss, progressive fatigue and muscle weakness. A 43-year-old Caucasian woman was referred to our hospital by her physician for suspected contact dermatitis since she described mild itching sensations in her arms and legs as her major symptom. A physical examination revealed erythematous papular lesions over her metacarpophalangeal and proximal interphalangeal joints together with a periungual involvement with redness, hyperkeratosis and capillary telangiectasia along the distal nailfolds on her hands. She was unaware of these features and they did not seem to bother her. A thorough examination of her medical history, however, revealed more symptoms. Pain and weakness in the muscles of her proximal extremities and neck flexor muscles led to difficulty in raising her arms and climbing stairs. At the same time she experienced swallowing difficulties and reported an uncharacteristic weight loss of 10 kg in the last 3 months. The results of laboratory tests showed increased values of serum creatine kinase and myoglobin. An electromyogram, a skin biopsy and a muscle biopsy confirmed the diagnosis of dermatomyositis. A computed tomography of her thorax showed a nodular mass in the upper lobe of her right lung. A histological examination of the lung biopsy showed an adenocarcinoma of moderate differentiation. She was diagnosed with paraneoplastic dermatomyositis as the first sign of a lung adenocarcinoma. Conclusions Our case report highlights the importance of a thorough search for underlying malignancy in patients with dermatomyositis even if dermatomyositis has a mild appearance or a discrete skin manifestation.